2022
DOI: 10.3390/educsci12080508
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning Phenomenon: From the Perspective of Learning Facilities, Curriculum, and Character of Elementary School Students

Abstract: This article aimed to describe the online learning phenomenon from the perspective of learning facilities, curriculum, and students’ characters in schools and the correlation among those three variables. This research employed a qualitative descriptive method. The data were collected through interviews, observations, and questionnaires. The research subject was the fifth-grade class of an elementary school in Palembang, which consisted of 19 students’ parents, 8 teachers, and 47 students. The findings showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Research shows that, in general, students' perceptions of introductory material regarding material related to tourism facilities and services in English in teaching the English for Tours and Travel course are good, as shown by the largest percentage of scores obtained. Students in the English for Tours and Travel course positively perceive the material introducing tourism facilities and services (Abdurrahmansyah et al, 2022;Taufan, 2022). They consider this material very relevant and useful in understanding the practical aspects of the tourism industry.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that, in general, students' perceptions of introductory material regarding material related to tourism facilities and services in English in teaching the English for Tours and Travel course are good, as shown by the largest percentage of scores obtained. Students in the English for Tours and Travel course positively perceive the material introducing tourism facilities and services (Abdurrahmansyah et al, 2022;Taufan, 2022). They consider this material very relevant and useful in understanding the practical aspects of the tourism industry.…”
Section: Discussionmentioning
confidence: 99%
“…According to Abdurrahmansyah et al, (2022) and Baticulon et al, (2021), obstacles that can be identified in online learning include technological constraints, individual constraints, local (domestic) constraints, institutional constraints, and social constraints. Technological constraints include constraints caused by hardware, software, and other things such as access quality, bandwidth, and access continuity components.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it can be interpreted that morality is a trait that is embedded in the human soul that can give birth to good or bad deeds spontaneously without the need for thought and encouragement from outside. Likewise, character can be built through habituation by the teacher, utilizing intensive interaction with students at school (Abdurrahmansyah et al, 2022). Children's moral is influenced by their environment (Dunn, 1988).…”
Section: Moralsmentioning
confidence: 99%